Concept Cars as Vehicles for Change in SMEs - Javier Ricardo Mejía Sarmiento; Gert Pasman; Erik Jan Hultink; Pieter Jan Stappers (Temes de Disseny)
Making prototypes of fictitious artifacts has long been applied in corporations as a design-led way to envisioning the future. These techniques make use of design to explore speculative futures translating abstract questions into concrete objects and bringing the human dimension and experience into futures techniques. The design-led strategic foresight techniques follow making activities – including visual synthesis, prototyping and storytelling – and result in experimental and experiential artifacts offering concrete, hands-on and specific images of the futures. An example of these techniques is the making and sharing of concept cars, a long-standing practice in the automotive industry. These artifacts facilitate the sharing of future visions, which embody future ideas, to diverse people.